Adaptive Virtual Reality Solutions: A Literature Review - Correia, Pedro Henrique Barcha (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
Virtual Reality technology emerges as a versatile tool with applications ranging from gaming to therapy. Particularly, Adaptive Virtual Reality (AVR) stands out as a promising field, employing adaptive mechanisms to automatically customize the user experience according to individual preferences and needs. The use cases for this technology are broad, and so is the technical landscape. AVR technology enables, for instance, educational platforms that adapt to the user’s learning style, upper limb rehabilitation with auto-adjustable difficulty, and horror games that detect and incorporate the user’s most feared elements. Implementation-wise, some studies utilize Neural Networks and Support Vector Machines to adapt the system’s logic, while others use Fuzzy Logic Systems, for example. Additionally, some works integrate physiological sensors to estimate user stress, cognitive workload, or cybersickness. This technological and practical diversity poses a challenge for researchers and developers seeking to build AVR-based applications. To assist these professionals, this work reviews 30 studies that propose, develop, and assess AVR-based solutions. It provides a technological overview of these systems and classifies them into four domain groups: healthcare, learning/training, entertainment, and cybersickness mitigation. This work also presents key considerations and guidelines for designing and assessing AVR-based systems.